3D coupled wind-induced inelastic response of base-isolated tall buildings with eccentricity and biaxial interaction of hysteretic restoring base forces. Issue 232 (January 2023) - Tian, Jingying; Chen, Xinzhong
Abstract: This study presents an analysis framework for coupled inelastic response of base-isolated tall buildings with eccentricities of mass and resistance and coupled hysteretic restoring forces of base isolation system. The upper building motion is represented by lower modal displacements. The translational hysteretic restoring forces of base isolation system are described by a biaxial hysteretic model and the torsional restoring moment by a linear elastic model. The stochastic story wind forces of the upper building are represented in their cross power spectral matrix. Response history analysis is carried out to characterize the coupled responses of a square-shaped tall building with eccentricity in the center of resistance. The results showed that the eccentricity amplifies the alongwind response but has relatively less influence on the larger crosswind and torsional responses. The eccentricity has less influence on the inelastic response of based-isolated building as compared to the fixed-base building. The base isolation with inelastic response is more effective for building with eccentricity as compared to building without eccentricity. The biaxial interaction reduces the effect of eccentricity on base displacements but increases the effect on upper building response. The eccentricity and biaxal interaction result in fast growth of time-varying mean alongwind base displacement. Highlights: This study presents an analysis framework for coupled inelastic response of base-isolated tall buildings with eccentricities and coupled hysteretic restoring forces of base isolation system. The translational hysteretic restoring forces of base isolation system are described by a biaxial hysteretic model and the torsional restoring moment by a linear elastic model. Reponse history analysis is performed to characterize the coupled responses of a square-shaped tall building with eccentricity in the center of resistance. The eccentricity has less effect on the response of based-isolated building as compared to the fixed-base building. The base isolation is more effective for building with eccentricity. The biaxial interaction reduces the effect of eccentricity on base displacements. The eccentricity and biaxal interaction lead to fast growth of time-varying mean alongwind base displacement.